2014
DOI: 10.3892/or.2014.3573
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the FIB-4 index for non-B non-C hepatocellular carcinoma treated with surgical resection

Abstract: Abstract. The aims of the present study were to examine the relationship between the preoperative FIB-4 index and background liver fibrosis in non-tumor parts obtained from surgical specimens and to investigate whether the FIB-4 index can be a useful predictor for non-B non-C hepatocellular carcinoma (NBNC-HCC) patients treated with surgical resection (SR). A total of 118 patients with NBNC-HCC treated with SR with curative intent were analyzed. Receiver operating characteristic (ROC) curve analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
1
4
0
1
Order By: Relevance
“…As identified in previous studies [ 8 , 10 , 12 14 , 19 ] on noninvasive markers for prediction prognosis, the present study also concludes that fibrosis-4 is able to offer a better overall prediction with regard to survival and disease-free survival for HCC patients subjected to liver resection. In addition, a further difference was observed in the present study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As identified in previous studies [ 8 , 10 , 12 14 , 19 ] on noninvasive markers for prediction prognosis, the present study also concludes that fibrosis-4 is able to offer a better overall prediction with regard to survival and disease-free survival for HCC patients subjected to liver resection. In addition, a further difference was observed in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…However, the conclusions from these studies remain controversial. Whilst some studies reported that fibrosis-4 [ 8 , 10 , 12 14 ] provided optimum discrimination capability with respect to liver cirrhosis and also appeared to offer capabilities with respect to predicting long-term outcomes, the study conducted by Choi [ 6 ] indicated that the Forn index was the optimum biomarker, whilst Pang [ 11 ] identified King's score as the optimum option. Therefore, the aim of this paper is to determine whether such noninvasive models have the ability to predict cirrhosis, postoperative complications, and survival in patients presenting with HCC and undergoing hepatectomy with R0 intent and also to determine the optimum approach.…”
Section: Introductionmentioning
confidence: 99%
“…The same as the other fibrosis indexes, FIB-4 has been proved to accurately predict cirrhosis and be an independent prognostic factor for survival and disease-free survival for HCC patients in many studies [19][20][21]. Moreover, several studies [7,12] also found that increased preoperative FIB-4 or APRI may be a predictor of postoperative hepatic failure.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, we previously reported that the GSA index as defined by the uptake ratio of the liver to the liver plus heart at 15 min to the uptake ratio of the heart at 15 min to that at 3 min ratio calculated from 99mTc-labeled diethylene triamine pentaacetate-galactosyl human serum albumin (99mTc-GSA) scintigraphy yielded the highest area under the receiver operating curve (AUROC) for predicting histologically proven cirrhosis with a level of 0.786 at an optimal cut-off value of 1.37 (sensitivity: 65.9%; specificity: 79.0%) in HCV-related HCC patient treated with surgical resection (SR) ( n = 213) and it can be a useful predictor for HCC recurrence after surgery [ 32 ]. Furthermore, in non-B and non-C HCC patients treated with SR ( n = 118), we have shown that the FIB-4 index yielded the highest AUROC for histologically proven cirrhosis with a level of 0.887 at an optimal cut-off value of 2.97 (sensitivity: 92.3%; specificity: 69.6%), and FIB-4 index >2.97 ( P = 0.044) was a significant independent factor linked to HCC recurrence [ 33 ].…”
Section: Noninvasive Methods For Predicting Lc or Lc Related Complmentioning
confidence: 99%